B(C6F5)(3): catalyst or initiator? insights from computational studies into surrogate silicon chemistry - Banerjee, Subhrashis; Vanka, Kumar (ACS Catalysis, 2018)
One of the most promising recent developments in catalysis has been the use of the metal-free Lewis acid B(C6F5)(3) as a catalyst for a range of different chemical transformations. Perhaps the most impressive achievement in this regard is the recently accomplished in situ generation of SiH4 from surrogates (Simonneau and Oestreich, Nat. Chem., 2015,7, 816). However, what the current computational work, with density functional theory, reveals is that this process, in addition to being catalyzed by B(C6F5)(3), is also significantly dominated by a series of autocatalytic reactions. The results are further corroborated by the use of the energetic span model, which shows that the turnover frequency is higher for the newly proposed autocatalytic pathway in comparison to the conventional B(C6F5)(3)-catalyzed pathway. The current work therefore provides interesting new insights into surrogate silicon chemistry. But, more importantly, the current studies indicate that B(C6F5)(3) is likely to function more as an initiator rather than a pure catalyst in many metal-free transformations that have been reported to date.
Keywords: autocatalysis; Density functional theory; ion-pair; Lewis acid catalysis; reaction mechanism; surrogate silicone chemistry; tris(pentafluorophenyl)borane

Beyond hydrofunctionalisation: a well-defined calcium compound catalysed mild and efficient carbonyl cyanosilylation - Yadav, Sandeep; Dixit, Ruchi; Vanka, Kumar; Sen, Sakya S. (Chemistry-A European Journal, 2018)
Organocalcium compounds have been reported as efficient catalysts for various transformations, for cases in which one of the substrates contained an E-H (E=B, N, Si, P) bond. Here, we look at the possibility of employing an organocalcium compound for a transformation in which none of the precursors has a polar E-H bond. This study demonstrates the utilization of a well-defined amidinatocalcium iodide, [PhC(NiPr)(2)CaI] (1) for cyanosilylation of a variety of aldehydes and ketones with Me3SiCN under ambient conditions without the need of any co-catalyst. The reaction mechanism involves a weak adduct formation between 1 and Me3SiCN leading to the activation of the Si-C bond, which subsequently undergoes sigma-bond metathesis with a C=O moiety. Such a mechanistic pathway is unprecedented in alkaline earth metal chemistry. Experimental and computational studies support the mechanism.
Keywords: Ca catalysis; carbonyls; cyanosilylation; Density functional calculations; transition-metal free

Bronsted acid-promoted cyclodimerization of α,β-unsaturated γ-ketoesters: construction of fused pyrano-ketal-lactones and γ-ylidene-butenolides - Vinodkumar, Ramavath; Nakate, Ashwini K.; Sharma, Himanshu; Vanka, Kumar; Rama Krishna, Gamidi; Kontham, Ravindar (ACS Omega, 2024)
Unprecedented MsOH-promoted diastereoselective cascade dimerization and intramolecular lactonization of readily accessible alpha,beta-unsaturated gamma-ketoesters are presented. The results obtained in this work, control experiments, and density functional theory (DFT) calculations suggested that the initial enolization and E to Z isomerization/equilibration of olefin (C=C) of substrate alpha,beta-unsaturated gamma-ketoesters give a Z-isomer preferentially over an E-isomer. Subsequently, the Z-isomer undergoes intermolecular annulation with alpha,beta-unsaturated gamma-ketoesters via domino Michael addition/ketalization/lactonization steps to furnish fused tetracyclic pyrano-ketal-lactone. However, the Z-isomer prefers intramolecular trans-esterification in a competing pathway and gives bicyclic gamma-ylidene-butenolide. The key features of this work include simple Br & oslash;nsted acid catalysis, the formation of three bonds, two rings, and three contiguous stereogenic centers in a single step, DFT calculations, and the assignment of relative stereochemistry through X-ray diffraction (XRD) and two-dimensional (2D) nuclear magnetic resonance (NMR) analyses.

Brønsted acid- and Ni(ii)-catalyzed C-H oxidation/rearrangement of cyclotriveratrylenes (CTVs) to cyclic and acyclic quinones as potential anti-cancer agents - Darole, Ratanamala S.; Choudhary, Shailendra Singh; Sharma, Himanshu; Mali, Bhupendra P.; Gopu, Booblan; Vanka, Kumar; Senthilkumar, Beeran (Organic and biomolecular chemistry, 2024)
This paper describes a simple and practical protocol for the direct synthesis of acyclic and cyclic quinone derivatives via an acid-promoted nickel(ii)-catalyzed inner rim C-H oxidation of cyclotriveratrylene (CTV) and its analogues. The cyclic quinone derivatives resulted from trimethoxy-cyclotriveratrylene (TCTV) through C-C bond formation via intramolecular ipso substitution followed by subsequent anionic rearrangement containing stereo-vicinal quaternary centers. The DFT calculations strongly support the experimental findings and reveal the role of Bronsted acids in the C-H bond activation of CTV. All the newly synthesized compounds were screened for their in vitro anti-cancer activity using colorimetric SRB assay analysis. Among them, compounds 3a, 3d, 3h, 4a, 4b, 4c and 4e exhibited moderate anticancer activity against A549, HCT-116, PC-3, MDA-MB-231, HEK-293 and SW620 human cancer cell lines.

Bioinspired synthesis of bridged isochromane fused pyrazoles by a silver catalyzed cascade reaction and its application for antibacterial activity - Singh, Bhuvnesh; Tewari, Shreya; Kaur, Manleen; Sharma, Himanshu; Vanka, Kumar; Singh, Neetu; Singh, Ravi P. (JACS Au, 2025)
A stereoselective silver catalyzed one pot vinylogous aldol addition followed by a cascade [4+2] cycloaddition reaction of α-arylidene pyrazolinones to in situ generated isochromenylium ions has been developed, which provides an unprecedented bridged [2.2.2] [3.3.1] pentacyclic [5-6-6-6-6] skeleton consisting of an isochroman, chroman, and a pyrazole unit in one molecule with good to high yields as a single diastereomer. This method offers mild reaction conditions, wide substrate compatibility, excellent scalability and easy derivatization. A DFT study was carried out to clarify the reaction mechanism. It was exciting to observe that the unprecedented bridged isochromans synthesized here have shown excellent selectivity toward Gram-positive and Gram-negative bacteria. We demonstrate that while some structures are broad spectrum antibacterial there are two distinct structures that can be explored for selective activity.
Keywords: Antibacterial; Bridged [2.2.2] [3.3.1]; ROS; Stereoselective; Vinylogous aldol addition; [4+2] cycloaddition